2020
DOI: 10.1159/000505333
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Carbenoxolone against Experimental Autoimmune Encephalomyelitis in a Mouse Model

Abstract: Introduction: Multiple sclerosis (MS) is a complex demyelinating disease involving central nervous system (CNS). It is still a challenge to secure an effective therapeutic strategy against this disease. Carbenoxolone (CBX) is a derivative of glycyrrhetinic acid, which is widely used in brain research for its gap-junction inhibition effects. Many researchers have observed CBX-mediated suppression of CNS inflammation in their studies. Objective: We want to further examine its anti-inflammation effects in CNS dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“… 34 Carbenoxolone, as a derivative of GA, significantly reversed the severity and pathology in experimental autoimmune encephalomyelitis. 35 IL-17-secreting and IFN-γ-secreting CD4 + T lymphocytes were remarkably lower in the spleen after carbenoxolone treatment in mice with experimental autoimmune encephalomyelitis. These data show that 18β-GA can regulate the homeostasis of CD4 + T helper cells, which is consistent with our research.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“… 34 Carbenoxolone, as a derivative of GA, significantly reversed the severity and pathology in experimental autoimmune encephalomyelitis. 35 IL-17-secreting and IFN-γ-secreting CD4 + T lymphocytes were remarkably lower in the spleen after carbenoxolone treatment in mice with experimental autoimmune encephalomyelitis. These data show that 18β-GA can regulate the homeostasis of CD4 + T helper cells, which is consistent with our research.…”
Section: Discussionmentioning
confidence: 85%
“…Carbenoxolone (CBX), as a derivative of GA, significantly reversed the severity and pathology in experimental autoimmune encephalomyelitis (EAE) (35). IL-17-secreting and IFN-γ-secreting CD4 + T lymphocytes were remarkably lower in the spleen after CBX treatment in mice with EAE.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that CBX treatment decreases the reactive gliosis and scar formation after a needle-track injury model to the brain ( Andersson et al, 2011 ). Previous studies have shown that in the MOG EAE model, CBX treatment delays the onset of neurological symptoms and decreases the severity ( Shijie et al, 2009 ; Endong et al, 2011 ; Chen et al, 2020 ). The authors explain the beneficial effects of CBX by lowering the production of interleukin (IL)-23 and, therefore, the differentiation of T helper (TH)-1 and TH-17, protecting from excitotoxicity by inhibiting glutamate release from microglia and increasing brain-derived neurotrophic factor.…”
Section: Discussionmentioning
confidence: 99%
“…It also exerts its anti-fibrotic actions in the pancreatic and hepatic stellate cell cultures, which are very similar to brain pericytes hence they are named as hepatic and pancreatic pericytes ( Uyama et al, 2003 ; Masamune et al, 2013 ). Previous studies have shown that in the MOG EAE model, CBX treatment delays the onset and decreases the severity of neurological symptoms ( Shijie et al, 2009 ; Endong et al, 2011 ; Chen et al, 2020 ). Due to its anti-fibrotic effects as well as effects on satellite cells (pericytes of liver and pancreas) and possible role of fibrosis in EAE models pathophysiology, we want to detect antifibrotic effect of CBX on PLP induced EAE model and define possible therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Carbenoxolone, a gap junction blocker targeting Cx43, has been evaluated in animal models of MS. The authors found that carbenoxolone significantly reduced the severity of autoimmune encephalomyelitis (the most commonly applied model for MS) and reduced the quantity of inflammatory mediators ( Table 3 ) [ 150 ]. More studies are needed to see if modulation of Cx43 hemichannel activation in MS could aid in the progression of the disease.…”
Section: Clinical Correlationmentioning
confidence: 99%